ANALISIS KELAYAKAN FINANSIAL PEMBIBITAN SAPI PERANAKAN ONGOLE POLA GADUHAN - Novanda, Ridha Rizki (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
Gaduhan is one of agribusiness pattern committed by farmers for assistance in his business capital. Andini Muyo livestock group has received government assistance in the form of funds to implement PSBP and PPBB. Cattle breeders were given to members’ group by profit-sharing system. This research was aimed at analysing the financial feasibility of cattle breeder bussiness on “penggaduh” system after receiving two types of PSBP assistances and its sensitivity. Data dari fourty seven respondents censused were analysed descriptive and quantitively using NPV, IRR, PP, Net B/C, and Gross B/C indicators. The results showed that the gaduhan system was unfeasible financially.